A low-temperature fuel cell composite electrolyte based on core-shell limited non-equivalent interface and a preparation method thereof
Patent Information
- Application Number
- CN202611115433.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-16
AI Technical Summary
[0026]有鉴于此,本发明提供一种基于核壳限域非等效双界面的低温燃料电池复合电解质及其制备方法,以解决或缓解现有技术中存在的技术问题,至少提供一种有益的选择
[0094] I. This invention significantly reduces the interfacial instability caused by the random distribution of carbonate phase through core-shell confinement treatment. The non-equivalent dual-interface structure is conducive to the formation of continuous or quasi-continuous interfacial transport channels, improving ion migration efficiency under low temperature conditions. The dual-interface effect helps to improve charge selectivity, reduce the risk of electron penetration, and simultaneously improve the transport and interfacial dynamics and electron blocking ability of the composite electrolyte, thereby reducing the total impedance.
Smart Images

Figure CN122930964A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of fuel cell composite electrolyte design and interface control technology, specifically to a low-temperature fuel cell composite electrolyte based on a core-shell confined non-equivalent dual interface and its preparation method. Background Technology
[0002] As a highly efficient and clean energy conversion device, fuel cells have advantages such as high energy conversion efficiency, strong fuel adaptability and environmental friendliness, and have broad application prospects in fields such as distributed energy, portable power sources and transportation power.
[0003] For low-temperature or medium-low-temperature solid oxide fuel cells, lowering the operating temperature helps to improve system life, shorten start-up time, and reduce packaging and system costs, but it also brings problems such as insufficient electrolyte ion conductivity and increased interface polarization.
[0004] In existing technologies, cerium oxide-based materials are widely used in low-temperature electrolyte systems due to their high oxygen ion conductivity.
[0005] However, cerium oxide doped systems are prone to Ce oxidation under reducing atmospheres. 4+ Partial reduction leads to increased electron leakage.
[0006] This problem is particularly prominent in cryogenic fuel cells that emphasize high output voltage and high power density, and it can easily lead to a drop in open-circuit voltage, an increase in internal short-circuit losses, and a decrease in energy conversion efficiency.
[0007] To address the aforementioned issues, existing technologies attempt to combine cerium oxide with carbonate phases, utilizing interface-induced ion transport to improve low-temperature performance.
[0008] Numerous studies have shown that in the cerium oxide-carbonate system, the key factor is not just the individual phases themselves, but the interfacial region formed between the two phases.
[0009] The interface region can not only provide faster ion migration channels, but may also improve charge selectivity through interface charge redistribution.
[0010] However, existing cerium oxide-carbonate composite electrolytes still have the following problems:
[0011] 1. The interface is randomly distributed and lacks repetition.
[0012] Traditional mechanical mixing, one-step co-precipitation, or simple compounding methods often result in the random attachment of the carbonate phase to the oxide surface. The interface position, coverage, and connectivity are difficult to control precisely, leading to large performance fluctuations between sample batches.
[0013] 2. The interface is clearly equivalent, but the controllability is limited.
[0014] Existing composite systems mostly rely on randomly formed carbonate / cerium oxide interfaces, which are relatively simple in type and lack clear spatial division of labor and functional differences between different interfaces, making it difficult to simultaneously achieve multiple objectives such as enhanced ion transport, suppression of electron leakage, and reduction of polarization loss.
[0015] 3. Insufficient functionality of dual interfaces
[0016] For cerium oxide-based doped materials, simply increasing the oxygen defect concentration or the number of carbonate interfaces may introduce the risk of electron penetration while promoting ion migration. Without controllable interfacial charge redistribution and local electrostatic barriers, it is difficult to selectively regulate ion transport and electron blocking.
[0017] 4. Insufficient structural stability
[0018] The distribution of carbonates in a composite system is strongly influenced by the preparation route. If there is a lack of stable framework constraints, the interface may migrate, aggregate, or mismatch during subsequent preparation or operation, thereby weakening the continuity and stability of the interface transport network.
[0019] 4. Limited output performance
[0020] Due to the lack of a clear and sustainable interfacial transport network, many composite electrolytes, although possessing a certain degree of ionic conductivity, still exhibit insufficient power density, high ohmic impedance, or excessive polarization loss in actual battery output.
[0021] Therefore, from a patent and engineering perspective, simply emphasizing "a higher result in a certain test" is insufficient to establish a stable inventive point. A more reasonable approach would be:
[0022] First, a stable first interface skeleton is constructed using a core-shell confinement method.
[0023] Then, a second cerium oxide phase is introduced to form a second interface with different composition and charge environment.
[0024] Finally, a non-equivalent dual-interface network was constructed to achieve a synergistic unification of enhanced ion migration, suppressed electron leakage, and improved fuel cell output performance.
[0025] To this end, a low-temperature fuel cell composite electrolyte based on a core-shell confined non-equivalent dual interface and its preparation method are proposed. Summary of the Invention
[0026] In view of this, the present invention provides a low-temperature fuel cell composite electrolyte based on a core-shell confined non-equivalent dual interface and its preparation method, so as to solve or alleviate the technical problems existing in the prior art, and at least provide a beneficial option.
[0027] The technical solution of this invention is achieved as follows: a low-temperature fuel cell composite electrolyte based on a core-shell confined non-equivalent dual interface and its preparation method, comprising the following steps:
[0028] S1. Prepare zirconium-yttrium co-doped cerium oxide framework material to obtain the first inorganic ion framework powder with oxygen ion conductivity;
[0029] S2. A barium carbonate shell layer is deposited in situ on the surface of the first inorganic ion framework powder to obtain a barium carbonate-coated core-shell framework powder, so as to form a barium carbonate / zirconium yttrium co-doped cerium oxide first interface.
[0030] S3. Preparation of neodymium-doped cerium oxide second cerium oxide phase powder;
[0031] S4. The core-shell structure framework powder obtained in step S2 and the second cerium oxide phase powder obtained in step S3 are mixed and compounded according to a preset mass ratio, so that the barium carbonate shell layer and the second cerium oxide phase powder come into contact and form a barium carbonate / neodymium-doped cerium oxide second interface, thereby obtaining a non-equivalent dual-interface composite electrolyte powder that simultaneously has a barium carbonate / zirconium-yttrium co-doped cerium oxide first interface and a barium carbonate / neodymium-doped cerium oxide second interface;
[0032] S5. Introduce the non-equivalent dual-interface composite electrolyte powder as an electrolyte layer into the fuel cell structure to construct a low-temperature fuel cell single cell.
[0033] S6. The fuel cell is operated under hydrogen / air or equivalent reducing / oxidizing atmosphere conditions, so that the dual interfaces in the dual-interface composite electrolyte can synergistically regulate ion transport and charge selectivity, thereby improving the output performance of the fuel cell.
[0034] More preferably, in step S1, the chemical composition of the zirconium-yttrium co-doped cerium oxide framework material is as follows:
[0035] Zr 0.1 Y 0.2 Ce 0.7 O 2-δ That is, (ZYDC);
[0036] The framework material is prepared by a co-precipitation method, including the following process:
[0037] A mixed metal salt solution is formed by dissolving soluble precursors containing Ce, Zr, and Y in deionized water.
[0038] A coprecipitation reaction occurs in the presence of an alkaline precipitant, forming a precursor precipitate containing Ce, Zr, and Y;
[0039] The precursor precipitate was washed, dried, and calcined to obtain the zirconium-yttrium co-doped cerium oxide framework material;
[0040] The precursor is preferably a nitrate, and the precipitant is preferably ammonium bicarbonate.
[0041] More preferably, in step S2, the barium carbonate shell is deposited in situ on the surface of the zirconium-yttrium co-doped cerium oxide framework material via a two-step precipitation method, comprising the following processes:
[0042] The skeleton powder obtained in step S1 is redispersed in a liquid medium;
[0043] Add a soluble barium salt containing Ba²⁺ to the dispersion so that Ba²⁺ is preferentially adsorbed onto the surface of the framework powder;
[0044] Adding a carbonate source under weakly alkaline and low supersaturation conditions allows barium carbonate to preferentially undergo heterogeneous nucleation and deposition on the framework surface.
[0045] After washing, drying and stabilization, BaCO3@ZYDC core-shell structured powder was obtained;
[0046] Among them, the Ba-containing 2+ The soluble barium salt is preferably barium nitrate, and the carbonate source is preferably ammonium bicarbonate.
[0047] The two-step precipitation method uses Ba 2+ Surface pre-adsorption and carbonate low supersaturation-induced deposition confine barium carbonate distribution on the ZYDC framework surface, thereby inhibiting random nucleation and free aggregation of the carbonate phase in the bulk solution.
[0048] More preferably, in step S3, the chemical composition of the neodymium-doped cerium oxide second cerium oxide phase powder is as follows:
[0049] Nd 0.05 Ce 0.95 O2, i.e. (NDC),
[0050] The neodymium-doped cerium oxide second phase powder is prepared by the sol-gel method, including the following process:
[0051] The Nd source and Ce source were dissolved in deionized water to form a mixed cation solution;
[0052] A complexing agent and a gelling agent are added to the mixed cationic solution to form a homogeneous precursor sol;
[0053] The sol was heated and concentrated to obtain a gel;
[0054] The neodymium-doped cerium oxide second phase powder was obtained by drying, pre-decomposing and calcining the gel;
[0055] The complexing agent is preferably one or both of EDTA and citric acid.
[0056] More preferably, in step S4, the mass ratio of the BaCO3@ZYDC core-shell structure powder to the NDC powder is:
[0057] (6~8):(4~2), preferably 7:3;
[0058] In BaCO3@ZYDC core-shell structured powder, the barium carbonate shell forms a continuous or quasi-continuous BaCO3 / NDC second interface contact network with the NDC powder.
[0059] The first interface of BaCO3 / ZYDC is a pre-constructed core-shell confinement interface, and the second interface of BaCO3 / NDC is a coupling interface formed during the subsequent recombination process. The first interface and the second interface are different from each other in terms of composition environment, spatial position and interface charge distribution, thus forming a non-equivalent dual-interface structure.
[0060] More preferably, in step S5, the fuel cell is assembled using a symmetrical structure or an equivalent sandwich structure, the structure including:
[0061] Anode layer;
[0062] Electrolyte layer;
[0063] Cathode layer;
[0064] The electrolyte layer is composed of non-equivalent dual-interface composite electrolyte powder obtained in step S4.
[0065] The anode layer and cathode layer are preferably made of Ni. 0.8 Co 0.15 Al 0.05 Li 0.02 A composite electrode layer formed by O2 (NCAL) and nickel foam.
[0066] The single cell is assembled by a one-step co-pressure method, with a pressing pressure of 100-300 MPa, preferably 200 MPa.
[0067] More preferably, in step S6, the operating temperature of the cryogenic fuel cell is 430–550°C.
[0068] Hydrogen or hydrogen-containing fuel gas is introduced into the anode side, and air or oxygen-containing gas is introduced into the cathode side.
[0069] The gas flow rate was controlled within the range of 150–200 mL·min⁻¹;
[0070] The non-equivalent dual-interface action includes at least one or more of the following mechanisms:
[0071] Promotes oxygen ion transport;
[0072] Promotes the co-migration of protons and oxygen ions;
[0073] Improve charge redistribution at the interface;
[0074] A local electrostatic barrier is formed;
[0075] Improve charge selectivity;
[0076] Suppress electron leakage;
[0077] Reduce ohmic impedance;
[0078] Reduce polarization loss.
[0079] More preferably, the non-equivalent dual-interface composite electrolyte formed in steps S2 to S4 satisfies at least three of the following structural features:
[0080] Maintain the main framework of the cerium oxide-based fluorite structure;
[0081] Barium carbonate is distributed on the surface of the framework particles in the form of a shell or interfacial phase;
[0082] A close nanoscale contact is formed between NDC and BaCO3@ZYDC;
[0083] The first interface of barium carbonate / ZYDC and the second interface of barium carbonate / NDC coexist;
[0084] The first interface of barium carbonate / ZYDC and the second interface of barium carbonate / NDC are non-equivalent interfaces;
[0085] No obvious impurity phase interconnected network appears;
[0086] No continuous electron leakage path is formed;
[0087] Networks with continuous or quasi-continuous ion transport interfaces.
[0088] More preferably, the method further includes a compound ratio optimization step, namely:
[0089] S7. Perform output performance testing, open-circuit voltage testing, and impedance analysis on cryogenic fuel cells obtained with different BaCO3@ZYDC to NDC mass ratios.
[0090] S8. Determine the optimal composite ratio by using at least two of the following criteria: maximum power density, open-circuit voltage, ohmic impedance, and polarization impedance.
[0091] The preferred composite ratio is 7BZ@ZYDC-3NDC.
[0092] The preferred composite ratio is used to achieve a balance between the number of interfaces, interface continuity, and function between the core-shell confined first interface and the coupled second interface.
[0093] The embodiments of the present invention have the following advantages due to the adoption of the above technical solutions:
[0094] I. This invention significantly reduces the interfacial instability caused by the random distribution of carbonate phase through core-shell confinement treatment. The non-equivalent dual-interface structure is conducive to the formation of continuous or quasi-continuous interfacial transport channels, improving ion migration efficiency under low temperature conditions. The dual-interface effect helps to improve charge selectivity, reduce the risk of electron penetration, and simultaneously improve the transport and interfacial dynamics and electron blocking ability of the composite electrolyte, thereby reducing the total impedance.
[0095] Second, this invention achieves high power density and high open-circuit voltage even at lower operating temperatures. Due to the pre-constructed interface structure and controllable composite ratio, the sample consistency is superior to that of randomly mixed systems. This invention can be used in semiconductor-ion coupled fuel cells and other low-temperature composite electrolyte battery systems. Simultaneously, the non-equivalent dual-interface network can promote ion migration while suppressing electron leakage, which is beneficial for improving the output stability and operational reliability of low-temperature fuel cells.
[0096] The above overview is for illustrative purposes only and is not intended to be limiting in any way. In addition to the illustrative aspects, embodiments, and features described above, further aspects, embodiments, and features of the invention will become readily apparent from the accompanying drawings and the following detailed description. Attached Figure Description
[0097] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0098] Figure 1 This is a flowchart illustrating the overall process of the method of the present invention.
[0099] Figure 2 This is a schematic diagram illustrating the working mechanism of the dual-interface structure of the present invention;
[0100] Figure 3 This is a flowchart of the composite ratio optimization process of the present invention;
[0101] Figure 4 The XRD patterns of the composite electrolytes with different proportions obtained in this invention and the comparative sample are shown below.
[0102] Figure 5The images show the microstructure of the BZ@ZYDC and 7BZ@ZYDC-3NDC composite electrolytes obtained in this invention.
[0103] Figure 6 The electrochemical performance diagrams are for composite electrolyte fuel cells with different and preferred ratios obtained in this invention.
[0104] Figure 7 The structural stability characterization diagram of the preferred ratio 7BZ@ZYDC-3NDC electrolyte of this invention after testing is shown. Detailed Implementation
[0105] In the following description, only certain exemplary embodiments are briefly described. As those skilled in the art will recognize, the described embodiments can be modified in various ways without departing from the spirit or scope of the invention. Therefore, the drawings and description are considered to be exemplary in nature and not restrictive.
[0106] The embodiments of the present invention will now be described in detail with reference to the accompanying drawings.
[0107] like Figure 1-7 As shown, this invention provides a low-temperature fuel cell composite electrolyte based on a core-shell confined non-equivalent dual interface and its preparation method, comprising the following steps:
[0108] S1. Prepare zirconium-yttrium co-doped cerium oxide framework material to obtain the first inorganic ion framework powder with oxygen ion conductivity;
[0109] S2. A barium carbonate shell layer is deposited in situ on the surface of the first inorganic ionic framework powder to obtain a core-shell structure framework powder coated with barium carbonate, so as to form the first interface of barium carbonate / zirconium yttrium co-doped cerium oxide.
[0110] S3. Preparation of neodymium-doped cerium oxide second cerium oxide phase powder;
[0111] S4. The core-shell structure framework powder obtained in step S2 and the second cerium oxide phase powder obtained in step S3 are mixed and compounded according to a preset mass ratio, so that the barium carbonate shell layer and the neodymium-doped cerium oxide second cerium oxide phase powder come into contact and form a barium carbonate / neodymium-doped cerium oxide second interface, thereby obtaining a dual-interface composite electrolyte powder with both a barium carbonate / zirconium-yttrium co-doped cerium oxide interface and a barium carbonate / neodymium-doped cerium oxide interface.
[0112] S5. Non-equivalent dual-interface composite electrolyte powder is introduced as an electrolyte layer into the fuel cell structure to construct a low-temperature fuel cell single cell.
[0113] S6. Operating the cryogenic fuel cell under hydrogen / air or equivalent reducing / oxidizing atmosphere conditions enables the first and second interfaces in the non-equivalent dual-interface composite electrolyte to form a transport network, selectively regulating ion migration and electron transport, thereby improving the output performance of the cryogenic fuel cell.
[0114] In one embodiment, in step S1, the chemical composition of the zirconium-yttrium co-doped cerium oxide framework material is as follows:
[0115] Zr 0.1 Y 0.2 Ce 0.7 O 2-δ That is, (ZYDC);
[0116] The framework material was prepared by co-precipitation, including the following process:
[0117] A mixed metal salt solution is formed by dissolving soluble precursors containing Ce, Zr, and Y in deionized water.
[0118] A coprecipitation reaction occurs in the presence of an alkaline precipitant, forming a precursor precipitate containing Ce, Zr, and Y;
[0119] The precursor precipitate was washed, dried, and calcined to obtain a zirconium-yttrium co-doped cerium oxide framework material;
[0120] The soluble precursor is preferably a nitrate, and the alkaline precipitant is preferably ammonium bicarbonate.
[0121] Through the above Ba 2+ The surface pre-adsorption and carbonate low supersaturation induced deposition process confine and fix barium carbonate on the ZYDC framework surface, thereby forming a pre-constructed BaCO3 / ZYDC first interface and reducing the risk of random generation and aggregation of free carbonate particles.
[0122] In one embodiment, in step S2, the barium carbonate shell is deposited in situ on the surface of the zirconium-yttrium co-doped cerium oxide framework material via a two-step precipitation method, including the following process:
[0123] The skeleton powder obtained in step S1 is redispersed in a liquid medium;
[0124] Add a soluble barium salt containing Ba²⁺ to the dispersion to allow Ba²⁺ to be adsorbed onto the surface of the skeletal powder.
[0125] Adding a carbonate source under weakly alkaline and low supersaturation conditions allows barium carbonate to preferentially undergo heterogeneous nucleation and deposition on the framework surface.
[0126] After washing, drying and low-temperature stabilization, BaCO3@ZYDC core-shell structured powder was obtained;
[0127] Among them, containing Ba2+ The soluble barium salt is preferably barium nitrate, and the carbonate source is preferably ammonium bicarbonate.
[0128] In one embodiment, in step S3, the chemical composition of the neodymium-doped cerium oxide second cerium oxide phase powder is as follows:
[0129] Nd 0.05 Ce 0.95 O2, i.e. (NDC),
[0130] Neodymium-doped cerium oxide second phase powder was prepared by the sol-gel method, including the following process:
[0131] The Nd source and Ce source were dissolved in deionized water to form a mixed cation solution;
[0132] Complexing agents and gelling agents are added to a mixed cationic solution to form a homogeneous precursor sol;
[0133] The sol was concentrated by heating to obtain a gel;
[0134] The gel was dried, pre-decomposed, and calcined to obtain neodymium-doped cerium oxide second phase powder.
[0135] The complexing agent is preferably one or both of EDTA and citric acid.
[0136] In one embodiment, in step S4, the mass ratio of BaCO3@ZYDC core-shell structure powder to NDC powder is:
[0137] (6~8):(4~2), preferably 7:3;
[0138] The mixing and compounding are carried out by ball milling, wet dispersion mixing, dry shear mixing or a combination thereof, so that the barium carbonate shell in the BaCO3 / NDC core-shell structure powder at the second interface forms a continuous or quasi-continuous BaCO3 / NDC second interface contact network with the NDC powder.
[0139] In one embodiment, in step S5, the cryogenic fuel cell single cell is assembled using a symmetrical structure or an equivalent sandwich structure, the structure including:
[0140] Anode layer;
[0141] Electrolyte layer;
[0142] Cathode layer;
[0143] The electrolyte layer is composed of the non-equivalent dual-interface composite electrolyte powder obtained in step S4.
[0144] Ni is preferably used for the anode and cathode layers. 0.8 Co 0.15 Al0.05 Li 0.02 A composite electrode layer formed by O2 (NCAL) and nickel foam.
[0145] The single cell is assembled by a one-step co-pressure method, with a pressing pressure of 100-300 MPa, preferably 200 MPa.
[0146] In one embodiment, in step S6, the operating temperature of the cryogenic fuel cell is 430–550°C.
[0147] Hydrogen or hydrogen-containing fuel gas is introduced into the anode side, and air or oxygen-containing gas is introduced into the cathode side.
[0148] The gas flow rate was controlled at 150–200 mL / min. -1 Within the range;
[0149] Non-equivalent dual-interface actions include at least one or more of the following mechanisms:
[0150] Promotes oxygen ion transport;
[0151] Promotes the co-migration of protons and oxygen ions;
[0152] Improve charge redistribution at the interface;
[0153] Suppress electron leakage;
[0154] Reduce ohmic impedance;
[0155] Reduce polarization loss.
[0156] In one embodiment, the non-equivalent dual-interface composite electrolyte formed in steps S2 to S4 satisfies at least three of the following structural features:
[0157] Maintain the main framework of the cerium oxide-based fluorite structure;
[0158] Barium carbonate is distributed on the surface of the framework particles in the form of a shell or interfacial phase;
[0159] A close nanoscale contact is formed between NDC and BaCO3@ZYDC;
[0160] The first interface of barium carbonate / ZYDC and the second interface of barium carbonate / NDC coexist;
[0161] The first interface of barium carbonate / ZYDC and the second interface of barium carbonate / NDC are non-equivalent interfaces;
[0162] No obvious impurity phase interconnected network appears;
[0163] Networks with continuous or quasi-continuous ion transport interfaces.
[0164] In one embodiment, the method further includes a compound ratio optimization step, namely:
[0165] S7. Perform output performance testing, open-circuit voltage and impedance analysis on low-temperature fuel cells obtained with different BaCO3@ZYDC to NDC mass ratios.
[0166] S8. Determine the optimal composite ratio by using at least two of the following criteria: maximum power density, open-circuit voltage, ohmic impedance, and polarization impedance.
[0167] The preferred composite ratio is 7BZ@ZYDC-3NDC.
[0168] Example 1: Preparation of BaCO3@ZYDC core-shell framework
[0169] 1. Preparation of ZYDC framework powder
[0170] According to Zr 0.1 Y 0.2 Ce 0.7 O 2-δ According to the stoichiometric ratio, cerium nitrate, zirconium nitrate and yttrium nitrate are weighed out and dissolved in deionized water to form a mixed metal salt solution.
[0171] Ammonium bicarbonate precipitant is added to the solution under stirring conditions to control the system to be weakly alkaline, resulting in a co-precipitation reaction and the formation of a precursor precipitate.
[0172] The precursor was precipitated, washed, dried, and then calcined to obtain ZYDC framework powder.
[0173] 2. In-situ deposition of BaCO3 crust
[0174] The ZYDC framework powder was redispersed in deionized water, and barium nitrate solution was added to make Ba 2+ Adsorbed on the surface of the framework particles.
[0175] Ammonium bicarbonate was then slowly added, and under low supersaturation conditions, BaCO3 preferentially underwent heterogeneous deposition on the surface of ZYDC particles.
[0176] After washing, drying and stabilization, BaCO3@ZYDC core-shell structured powder was obtained.
[0177] 3. Results
[0178] The resulting powder can form a well-defined BaCO3 / ZYDC interface at the particle scale, rather than a random distribution of free carbonate particles.
[0179] Example 2: Preparation of NDC powder
[0180] Nd2 was prepared by sol-gel method 0.05 Ce0.95 O2 powder.
[0181] Neodymium nitrate and cerium nitrate were dissolved in deionized water, and EDTA and citric acid were added as complexing agents to uniformly complex the metal ions.
[0182] After being heated and concentrated to form a gel, the powder is dried, ground, and calcined to obtain NDC powder.
[0183] The obtained NDC powder has good dispersibility and a stable cerium oxide-based crystal phase structure.
[0184] Example 3: Preparation of a dual-interface composite electrolyte
[0185] The BaCO3@ZYDC core-shell powder obtained in Example 1 was mixed with the NDC powder obtained in Example 2 at different mass ratios to obtain:
[0186] 9BZ@ZYDC-1NDC;
[0187] 8BZ@ZYDC-2NDC;
[0188] 7BZ@ZYDC-3NDC;
[0189] 6BZ@ZYDC-4NDC;
[0190] 5BZ@ZYDC-5NDC.
[0191] A dual-interface composite electrolyte powder was obtained by wet ball milling dispersion followed by drying.
[0192] Among them, 7BZ@ZYDC-3NDC performed best in subsequent electrochemical tests.
[0193] Example 4: Characterization of material structure and electrochemical performance
[0194] The phase structure, microstructure and electrochemical performance of the material obtained in this embodiment were characterized.
[0195] 1. Phase structure analysis
[0196] X-ray diffraction (XRD) analysis was performed on the obtained ZYDC framework, NDC powder, and BZ@ZYDC-NDC composite electrolytes in different proportions. The results are as follows: Figure 4 As shown, Figure 4 a shows the XRD patterns of NDC and BZ@ZYDC, both exhibiting typical fluorite structure characteristic peaks, indicating that doping did not alter the bulk lattice structure of cerium oxide. Figure 4b shows the XRD patterns of BZ@ZYDC-NDC composites with different mass ratios. No obvious characteristic diffraction peaks of barium carbonate or other impurity phases were observed in any of the composite samples. This is attributed to the presence of barium carbonate in an amorphous or highly dispersed shell form, indicating that the core-shell structure design of this invention effectively suppresses the aggregation and long-range ordered growth of the carbonate phase. Figure 4 XPS full spectrum results of c showed that characteristic peaks of elements such as Ce, Zr, Y, Nd, Ba, C, and O were present in the composite sample, confirming the successful construction of the dual interface (BaCO3 / ZYDC and BaCO3 / NDC). Moreover, no significant abnormal shift in the chemical state of each element was observed, indicating good chemical compatibility among the components.
[0197] 2. Observation of microstructure and interface structure
[0198] The microstructure of the optimized 7BZ@ZYDC-3NDC composite electrolyte was observed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM), and the results are as follows: Figure 5 As shown, Figure 5 Image a shows the SEM image of the BZ@ZYDC core-shell structure, which reveals that the ZYDC particles are coated with a uniform and dense barium carbonate shell, confirming the effectiveness of the in-situ deposition method. Figure 5 b shows that in the 7BZ@ZYDC-3NDC composite, a uniform and close heterogeneous contact is formed between the NDC particles and the BZ@ZYDC core-shell particles. This nanoscale close contact provides a structural basis for constructing a continuous interfacial transport network. Figure 5 TEM and HRTEM images from CD further revealed the atomic-resolution structure at the particle interface. The interfacial transition region between the BZ@ZYDC and NDC phases can be clearly observed. The interface is well-bonded, with no obvious amorphous layer or impurity phase segregation, which is conducive to the rapid exchange and transport of ions at the interface.
[0199] 3. Fuel Cell Output Performance Testing
[0200] Different proportions of BZ@ZYDC-NDC composite electrolytes were assembled into fuel cell single cells, and their output performance was tested under a hydrogen / air atmosphere. The results are as follows: Figure 6 As shown, Figure 6A comparison of battery performance with composite electrolytes of different mass ratios revealed that the maximum power density initially increased and then decreased with increasing NDC content. The 7BZ@ZYDC-3NDC ratio exhibited the best output performance, with significantly higher maximum power density and open-circuit voltage compared to other ratios. This is attributed to the formation of a more continuous and synergistic ion transport network at this ratio between the dual interfaces (BaCO3 / ZYDC and BaCO3 / NDC), effectively reducing ohmic impedance and polarization loss, thus validating the technical effectiveness of the optimal composite ratios described in claims 5 and 9. Figure 6 b demonstrates the fuel cell performance of the 7BZ@ZYDC-3NDC electrolyte over a wide temperature range of 550°C to 430°C. Although the battery performance decreases with decreasing temperature, it still maintains a high power density and open-circuit voltage at a low temperature of 430°C, indicating that the dual-interface composite electrolyte of the present invention has excellent low-temperature ion conductivity and good thermal stability.
[0201] 4. Long-term operational stability and elemental distribution analysis
[0202] The tested NCAL||7BZ@ZYDC-3NDC||NCAL battery underwent SEM cross-sectional observation and EDS elemental analysis. The results are as follows: Figure 7 As shown, Figure 7 The results show that after electrochemical testing, the electrolyte layer and the electrode layer remained tightly bonded, with no obvious delamination or cracking, confirming that the composite electrolyte of the present invention has good interfacial compatibility and structural stability. Figure 7 bc shows SEM images of the 7BZ@ZYDC-3NDC electrolyte at different magnifications after testing. The electrolyte layer maintains a dense structure, and no obvious cracks or pores were observed, effectively suppressing the permeation of fuel gas. Figure 7 The EDS elemental distribution diagram of d shows that elements such as Ce, Zr, Nd, and Ba are uniformly distributed in the electrolyte layer without significant elemental segregation or phase separation. This further confirms the stability of the dual-interface structure of the present invention during long-term operation and thermal cycling, which is beneficial to extending the service life of the fuel cell.
[0203] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art can easily conceive of various variations or substitutions within the technical scope disclosed in the present invention, and these should all be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A low-temperature fuel cell composite electrolyte based on a core-shell confined non-equivalent dual interface and its preparation method, characterized in that: Includes the following steps: S1. Prepare zirconium-yttrium co-doped cerium oxide framework material to obtain the first inorganic ion framework powder with oxygen ion conductivity; S2. A barium carbonate shell layer is deposited in situ on the surface of the first inorganic ion framework powder to obtain a barium carbonate-coated core-shell framework powder, so as to form a barium carbonate / zirconium yttrium co-doped cerium oxide first interface. S3. Preparation of neodymium-doped cerium oxide second cerium oxide phase powder; S4. The core-shell structure framework powder obtained in step S2 and the second cerium oxide phase powder obtained in step S3 are mixed and compounded according to a preset mass ratio, so that the barium carbonate shell layer and the second cerium oxide phase powder come into contact and form a barium carbonate / neodymium-doped cerium oxide second interface, thereby obtaining a non-equivalent dual-interface composite electrolyte powder that simultaneously has a barium carbonate / zirconium-yttrium co-doped cerium oxide first interface and a barium carbonate / neodymium-doped cerium oxide second interface; S5. Introduce the non-equivalent dual-interface composite electrolyte powder as an electrolyte layer into the fuel cell structure to construct a low-temperature fuel cell single cell. S6. The cryogenic fuel cell is operated under hydrogen / air or equivalent reducing / oxidizing atmosphere conditions, so that the first and second interfaces in the non-equivalent dual-interface composite electrolyte form a transport network, selectively regulating ion migration and electron transport, thereby improving the output performance of the cryogenic fuel cell.
2. The low-temperature fuel cell composite electrolyte based on a core-shell confined non-equivalent dual interface and its preparation method according to claim 1, characterized in that... In step S1, the chemical composition of the zirconium-yttrium co-doped cerium oxide framework material is as follows: Zr 0.1 Y 0.2 Ce 0.7 O 2−δ , that is (ZYDC); The framework material is prepared by a co-precipitation method, including the following process: A mixed metal salt solution is formed by dissolving soluble precursors containing Ce, Zr, and Y in deionized water. A coprecipitation reaction occurs in the presence of an alkaline precipitant, forming a precursor precipitate containing Ce, Zr, and Y; The precursor precipitate was washed, dried, and calcined to obtain the zirconium-yttrium co-doped cerium oxide framework material; The soluble precursor is preferably a nitrate, and the alkaline precipitant is preferably ammonium bicarbonate.
3. The low-temperature fuel cell composite electrolyte based on a core-shell confined non-equivalent dual interface and its preparation method according to claim 1, characterized in that: In step S2, the barium carbonate shell is deposited in situ on the surface of the zirconium-yttrium co-doped cerium oxide framework material via a two-step precipitation method, including the following process: The skeleton powder obtained in step S1 is redispersed in a liquid medium; Add a soluble barium salt containing Ba²⁺ to the dispersion, so that Ba… 2+ Preferentially adsorbed onto the surface of the skeleton powder; Adding a carbonate source under weakly alkaline and low supersaturation conditions allows barium carbonate to preferentially undergo heterogeneous nucleation and deposition on the framework surface. After washing, drying and low-temperature stabilization, BaCO3@ZYDC core-shell structured powder was obtained; Among them, the Ba-containing 2+ The soluble barium salt is preferably barium nitrate, and the carbonate source is preferably ammonium bicarbonate. The two-step precipitation method uses Ba 2+ Surface pre-adsorption and carbonate low supersaturation-induced deposition confine barium carbonate distribution on the ZYDC framework surface, thereby inhibiting random nucleation and free aggregation of the carbonate phase in the bulk solution.
4. The low-temperature fuel cell composite electrolyte based on a core-shell confined non-equivalent dual interface and its preparation method according to claim 1, characterized in that: In step S3, the chemical composition of the neodymium-doped cerium oxide second cerium oxide phase powder is as follows: Nd 0.05 Ce 0.95 O2, i.e. (NDC); The neodymium-doped cerium oxide second phase powder is prepared by the sol-gel method, including the following process: The Nd source and Ce source were dissolved in deionized water to form a mixed cation solution; A complexing agent and a gelling agent are added to the mixed cationic solution to form a homogeneous precursor sol; The sol was heated and concentrated to obtain a gel; The neodymium-doped cerium oxide second phase powder was obtained by drying, pre-decomposing and calcining the gel; The complexing agent and gelling agent are preferably one or both of EDTA and citric acid.
5. The low-temperature fuel cell composite electrolyte based on a core-shell confined non-equivalent dual interface and its preparation method according to claim 1, characterized in that: In step S4, the mass ratio of the BaCO3@ZYDC core-shell structure powder to the NDC powder is: (6~8):(4~2), preferably 7:3; The mixing and compounding are carried out by ball milling, wet dispersion mixing, dry shear mixing, or a combination thereof, so that the barium carbonate shell in the BaCO3@ZYDC core-shell structure powder forms a continuous or quasi-continuous BaCO3@ZYDC second interface contact network with the NDC powder.
6. The low-temperature fuel cell composite electrolyte based on a core-shell confined non-equivalent dual interface and its preparation method according to claim 1, characterized in that: In step S5, the fuel cell is assembled using a symmetrical structure or an equivalent sandwich structure, the structure including: Anode layer; Electrolyte layer; Cathode layer; The electrolyte layer is composed of non-equivalent dual-interface composite electrolyte powder obtained in step S4. The anode layer and cathode layer are preferably made of Ni. 0.8 Co 0.15 Al 0.05 Li 0.02 A composite electrode layer formed by O2 (NCAL) and nickel foam. The single cell is assembled by a one-step co-pressure method, with a pressing pressure of 100-300 MPa, preferably 200 MPa.
7. The method for synergistically improving fuel cell output performance through dual-interface collaboration according to claim 1, characterized in that: In step S6, the operating temperature of the fuel cell is 430–550°C. Hydrogen or hydrogen-containing fuel gas is introduced into the anode side, and air or oxygen-containing gas is introduced into the cathode side. The gas flow rate was controlled within the range of 150–200 mL·min⁻¹; The non-equivalent dual-interface action includes at least one or more of the following mechanisms: Promotes oxygen ion transport; Promotes the co-migration of protons and oxygen ions; Improve charge redistribution at the interface; A local electrostatic barrier is formed; Improve charge selectivity; Suppress electron leakage; Reduce ohmic impedance; Reduce polarization loss.
8. The low-temperature fuel cell composite electrolyte based on a core-shell confined non-equivalent dual interface and its preparation method according to claim 1, characterized in that: The non-equivalent dual-interface composite electrolyte formed in steps S2 to S4 satisfies at least three of the following structural features: Maintain the main framework of the cerium oxide-based fluorite structure; Barium carbonate is confined and distributed on the surface of the framework particles in the form of a shell or interfacial phase. A close nanoscale contact is formed between NDC and BaCO3@ZYDC; The first interface of BaCO3 / ZYDC and the second interface of BaCO3 / NDC coexist. The first interface of BaCO3 / ZYDC and the second interface of BaCO3 / NDC are not equivalent interfaces. No obvious impurity phase interconnected network appears; No continuous electron leakage path is formed; Networks with continuous or quasi-continuous ion transport interfaces.
9. The low-temperature fuel cell composite electrolyte based on a core-shell confined non-equivalent dual interface and its preparation method according to claim 1, characterized in that: The method further includes a compound ratio optimization step, namely: S7. Perform output performance testing, open-circuit voltage testing, and impedance analysis on cryogenic fuel cells obtained with different BaCO3@ZYDC to NDC mass ratios. S8. Use at least two of the following as screening criteria: maximum power density, open-circuit voltage, ohmic impedance, and polarization impedance to determine the optimal composite ratio. The preferred composite ratio is 7BaCO3@ZYDC-3NDC or 7BZ@ZYDC-3NDC. The preferred composite ratio is used to achieve a balance between the number of interfaces, interface continuity, and function between the core-shell confined first interface and the coupled second interface.